An urban park in teacher training (Simbiótica. Revista Eletrônica, 2025)
This article presents teacher training carried out within the scope of a Postgraduate Program, at the Federal Institute of Espírito Santo (Campus Vitória), with public basic education teachers in the area of Human Sciences, with emphasis on the area of Sociology. Through educational material, the objective is to analyze the educational and critical potential of the city's spaces, especially Parque Moscoso, an urban park located in the historic center of the city of Vitória/ES, and its interfaces with education, memory and the city. In general terms, we conclude that Parque Moscoso is an educational space that, through its memory and, depending on the mediations promoted, can reveal social contradictions that have been constituted together with the city's history.
Keywords: Teaching; Humanities; City; Teacher training